2022
DOI: 10.1038/s41598-022-18576-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of MMP9 transcription by ETS1 in immortalized salivary gland epithelial cells of patients with salivary hypofunction and primary Sjögren’s syndrome

Abstract: Primary Sjögren’s syndrome (pSS) patients exhibit enhanced degradation of the salivary epithelium initially through MMP9 overexpression. We assessed the expression of MMP9 and an associated transcription factor, ETS1, in primary salivary gland epithelial cells (SGECs) and investigated potential regulatory mechanism(s) in immortalized SGECs. SGECs and iSGECs were derived from pSS and/or xerostomic “sicca” patients. siRNA knockdown of ETS1 in iSGECs was performed to determine MMP9 mRNA (qRT-PCR) and protein expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…In patients with pSS, acinar and ductal cells have been shown to be responsible for local MMP9 secretion. [ 19 ] Furthermore, the glandular expression and activity of MMP9 are highly correlated with the degree and severity of salivary gland damage and functional alterations. [ 20 ] Interestingly, MMP9 expression was significantly decreased in mice with lung cancer treated with nobiletin.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with pSS, acinar and ductal cells have been shown to be responsible for local MMP9 secretion. [ 19 ] Furthermore, the glandular expression and activity of MMP9 are highly correlated with the degree and severity of salivary gland damage and functional alterations. [ 20 ] Interestingly, MMP9 expression was significantly decreased in mice with lung cancer treated with nobiletin.…”
Section: Discussionmentioning
confidence: 99%
“…MMP9 enhances new blood vessel formation by increasing smooth muscle migration and VEGF release, which eventually weakens the ber cap by degrading ECM, while simultaneously enhancing in ammatory response by increasing monocytes/macrophages swelling, which strongly diminishes plaque stability, thereby encouraging thrombosis formation [27][28][29]. Clinical trials revealed that the MMP-9 content in the salivary and lacrimal glands of pSS patients are strongly enhanced [30].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, ETS1 and MMP9 were found to be overexpressed in SGECs from patients with pSS. Further functional analysis demonstrated that ETS1 directly induced expression of MMP9 by exercising its TF activity and affected the expression of EMT markers in immortalized SGECs (iSGECs) from pSS [195]. In addition, the presence of EMT in SGEC from pSS patients was further strengthened by RNA sequencing data showing an over-representation of a pathway involving MMPs (collagen type III Alpha 1 chain (COL3A1), COL1A2 and A Disintegrin And Metalloproteinase with Thrombospondin Motifs (ADAMTS)) and core-EMT TF such as ZEB2 (Table 2) [196].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%